A new class of pseudo-random sequences from Mersenne numbers. (26th March 2009) - Mitra, Abhijit
A new class of pseudo random sequences is proposed that can be constructed from modulo-2 (mod 2) operations of two different maximal length sequences (m-sequences) where the period of the input sequences are Mersenne numbers. It is shown that the output sequences have certain properties to make these sequences effective in multi-user interference suppression and communication security.